IMPLEMENTASI PENGELOLAAN KEUANGAN DESA BERBASIS SISKEUDES DI DESA SRIMULYO KECAMATAN PIYUNGAN KABUPATEN BANTUL - Budiastuti, Atik; Anggraini, Oktiva; Kusumawiranti, Retno (Universitas Widya Mataram, 2022)
The purpose of this study was to determine the implementation of financial management based on Siskeudes in Srimulyo Village, Piyungan District, Bantul Regency. This type of research is a qualitative descriptive study, with data collection techniques including interviews, documentation, and observation. The implementation of village financial management in Srimulyo Village, Piyungan District, Bantul Regency, has paid attention to the principles of village financial management, namely: First, consistency of recording in accordance with the principles of village financial accounting. Second, involve the community in managing village finances. Third, transparency to give the community the right to know information related to village financial management. Fourth, the fulfillment of accountable village financial management. By using the Siskeudes application, village financial management can be implemented in a more informed, effective and efficient manner. However, there are still obstacles related to the Siskeudes application, namely Siskeudes can only be accessed in the village office environment, then when the application is off line and then on line, sometimes some data is lost. Likewise with consolidated reports, district governments still have to compile them manually because the consolidated report format in the Siskeudes cannot be used. District governments should further improve facilitation and assistance as well as training for village governments so that they can be better at managing village finances. The Siskeudes application can be further refined so that data loss does not occur again and the consolidated report format can also be used.